Hegel on the Margins: Derrida and the Relapse into Metaphysics - Wirsing, Claudia (Revista Eletrônica Estudos Hegelianos, 2022)
The question of how to begin a philosophical system belongs to the internal logic of every systematic philosophy and involves the notion of absolute presuppositions. This article deals with the concept of such a beginning in Hegel and Derrida. First, the article thematizes the aporia of beginning against the background of Kierkegaard’s critique of Hegel. Second, it focuses on the introductory sections of the “Doctrine of Essence” in Hegel’s Science of Logic, which have not received sufficient attention in relation to this topic so far. In these sections, Hegel raises the question of the relationship between immediacy and mediation, which he has made central to the question of beginning. I argue that in these sections Hegel offers an instructive alternative to theabsolutization and singularization of the beginning and the denial of its conceivability, while building a bridge to a “postmetaphysical” way of thinking that integrates critique with an awareness of the problem of ultimate metaphysical grounds. Finally, my key argument is that Derrida who, like Hegel, is critical of the notion of an absolute beginning still fails to escape the aporia of beginning with his concept of différance; and, consequently, in his critique of metaphysics, Derrida ends up returning to Hegel precisely at the moment when he tries the hardest to break from him.